Meningkatkan Peran Serta Masyarakat dalam Pengelolaan Desa Wisata Nglarang melalui Forum Group Discussion (FGD) - Nugroho, Dhimas Setyo; Saputra, Arif Dwi; Afif, Fuadi; Wahyuni, Amelia Tri; Hermawan, Hary (Jurnal Abdimas Pariwisata, 2025)
Enhancing Community Participation in the Management of Nglarang Tourism Village Through Forum Group Discussion (FGD) Community-based tourism village management is a key element in ensuring the sustainability of the local tourism industry. This article discusses the outcomes of a Forum Group Discussion (FGD) held in Nglarang Tourism Village, aimed at increasing community awareness and participation in tourism management. The event involved academics, practitioners, and local communities in formulating community-based tourism management strategies. Rejowinangun Tourism Village was used as a case study to demonstrate the success of economic sector clustering in tourism management. The FGD results indicate that active community participation and synergy among stakeholders are crucial in achieving sustainable tourism management. Through interactive discussions, an action plan was developed, including capacity-building programs, the establishment of an economic clustering system, and strengthened partnerships with academia and the private sector. The implementation of this approach is expected to transform Nglarang Tourism Village into a self-sustaining and sustainable tourism destination.